A robust SAR ATR algorithm using pulse coupled neural network - Sardar, Santu; Mishra, Amit K.; Srinu, Sesham (2014 Annual IEEE India Conference (INDICON), 2014)
Pulse coupled neural network (PCNN) framework is proposed in this paper for scale, position, elevation and illumination invariant synthetic aperture radar (SAR) automatic target recognition (ATR). We have used public release of the MSTAR dataset to validate our proposed system. We compared our proposed system performance with existing approaches and established the better performance of the proposed system. We have shown that, even with reduced training sets, the proposed system shows consistent performance whereas the performance of conventional systems degrades.